Strategi Pemasaran Produk Usaha Mikro, Kecil, dan Menengah (UMKM) Berbasis Ekonomi Syariah dalam Persaingan Global - Elisa Anita Farida (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2023)
This research was conducted to analyze the marketing strategy of UMKM in Indonesia to be able to compete in the international arena by using the concept of Islamic economics as a legal basis for implementing marketing strategies. The concept of Islamic economics in marketing strategy is a new and interesting thing to study, the trend of Islamic economics, both regional and global, is a positive conversation. The research method uses qualitative with a library research approach. Sources of data in this study were in the form of books, journals, previous research and other supporting sources relevant to this research. The focus of the study in this study includes sharia economic-based marketing, government policies in supporting UMKM and UMKM product marketing strategies using the basis of sharia economics in global competition. The results of this study show that sharia-based marketing has previous guidelines, although not yet clearly, regarding policies to support UMKM, real policies have been made for development, both through the commitment of general actors, adjusting rules, building an integrated database to monitoring.